2021
DOI: 10.1109/tvt.2021.3093822
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-Wave Radar Scheme With Passive Reflector for Uncontrolled Blind Urban Intersection

Abstract: Modern millimeter-wave automotive radars are employed to keep a safe distance between vehicles and reduce the collision risk when driving. Meanwhile, an on-board radar module is supposed to operate in the line-of-sight condition, which limits its sensing capabilities in intersections with obstructed visibility. Therefore, this paper investigates the scheme with passive reflector, enabling the automotive radar to detect an approaching vehicle in the non-line-of-sight (blind) urban intersection. First, extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Using several reflectors with optimized deployment, it has further been shown that even a less dense mmWave site deployment becomes feasible, even when using simpler non-reconfigurable passive reflectors [35]. Whereas these can also be deployed in the scope of 6G-enabled sensing services, as shown in [36], passive reflectors are typically considered for communication-centric purposes in the literature due to their simplistic set of features compared to other approaches, cf. Table I.…”
Section: Methods For Extending Mobile Radio Network Coverage To Black...mentioning
confidence: 99%
“…Using several reflectors with optimized deployment, it has further been shown that even a less dense mmWave site deployment becomes feasible, even when using simpler non-reconfigurable passive reflectors [35]. Whereas these can also be deployed in the scope of 6G-enabled sensing services, as shown in [36], passive reflectors are typically considered for communication-centric purposes in the literature due to their simplistic set of features compared to other approaches, cf. Table I.…”
Section: Methods For Extending Mobile Radio Network Coverage To Black...mentioning
confidence: 99%
“…Compared with LiDAR (light detection and ranging), cameras and optical sensors, the cost of millimeter-wave radar is low, since it only consists of an integrated circuit (IC) and printed antennas. Moreover, compared to traditional camera imaging systems, millimeter-wave radars are more effective in bad weather conditions (fog and rain) and nonline of sight (NLOS) target detection (curves on roads) 3,4 . Frequency-modulated continuous wave (FMCW) and fast chirp modulation (FCM) radars can be used to inherently measure ranges and relative velocities between a radar and targets 5,6 .…”
mentioning
confidence: 99%